An environmental approach to the Philippine revolution of 1896 conversion of autobiographies as historical texts - Diestro, Dwight David A. (2010)
Through the use of autobiographies as historical texts, the physical environment during the Revolution of 1896 can be portrayed. The writings of Isabelo de los Reyes, Santiago Alvarez, Carlos Ronquillo, Emilio Aguinaldo, and Pedro Paterno comprised the bases of the study. The sequencing of events from 1896 to 1897 was highlighted. The study included the causes/factors why the Revolution took place, actual cases and instances where the environment was foregrounded, and the general description of the environment as identity markers for the participants of the Revolution. The individual was a rich source of environmental descriptions. Alvarez, Ronquillo, and Aguinaldo were in the actual combat field; therefore when they mentioned environmental elements, they knew how to take advantage of what nature can provide in terms of choices to take. On the other hand, those engaged in agriculture in the circum-Manila area were described by de los Reyes. Among all of them, Paterno was different because nature was given immediate meaning based on his life experience here and abroad. He used it as a convenient source of metaphors. All history has an environmental dimension and the "self" through narratives can bequeath documentary evidence for historians to interpret.
Keywords: Philippine history, 1898-1945